The Effect of Mechanical Strain On the Electronic Conductivity of Α- Fe2O3: A Density Functional Theory Study - Abdulmutalib, Sheriff Naziru (AUC Knowledge Fountain, 2024)
Hydrogen has emerged as a promising future energy carrier due to its ability to produce zero carbon dioxide (CO2) emissions when burned. However, the limited natural abundance of hydrogen necessitates the development of cost-effective and environmentally friendly methods for large-scale hydrogen production. Among the different hydrogen production approaches, photoelectrochemical water splitting, which employs a photoanode material in a cell using solar energy to split water into hydrogen and oxygen, is the focus of this work. α-Fe2O3 (hematite) is a photoanode material that shows a promising future for hydrogen generation in a photoelectrochemical cells due to its cheapness, availability, and its capacity to absorb light within the range of visible spectrum. Nevertheless, when compared to other photoanode its main drawback is its overall low electronic conductivity, adversely affecting its activity as a photoanode material. Meanwhile, mechanical strain is known to modulate transport processes in materials including electronic conductivity. Herein, we aim to understand the effect of biaxial strain both compressive and tensile on changing the electronic conductivity of hematite. Prior work showed that in strain-free hematite slow small polarons predominates over fast large polarons (or free carriers) but they both co-exist. We explore the effect of biaxial mechanical strain on the electronic conductivity of hematite using density functional theory calculations with on-site Hubbard U terms on oxygen p-states and iron d-states. We apply biaxial strain in increments of 0.5% from −5% to +5% and find that the bandgap reduction occurs under both tensile and compressive strain, with a more significant reduction observed in the compressive strain state. We also observe an increase in free electron effective mass and a decrease in free hole effective mass as we move from the tensile to the compressive strain state. Moreover, we investigate the effect of mechanical strain on polarons of hematite and find out that it cannot change the energy landscape in favor of large polaron electrons (or free electrons). However, mechanical strain can alter the energy landscape in favor of large polaron holes (or free holes). This implies that applying slight compressive strain can enhance the overall electronic conductivity in hematite via reducing the band gap, increasing the concentration and the mobility of holes especially via large hole polarons while not significantly affecting the mobility of electrons. These findings provide insights into modulating the electronic conductivity of hematite, which can promote its use as a photocatalyst for hydrogen production, addressing the increasing energy demand and mitigating the impact of climate change.